Moral Injury and Religiosity in Active Duty U.S. Military with PTSD Symptoms. (2nd January 2019) - Volk, Fred; Koenig, Harold G.
ABSTRACT: This study examined the association between moral injury (MI) and religiosity, the modifying effects of PTSD severity on this relationship, and the receptivity to a spiritual intervention in 103 Active Duty U.S. Military (ADM). Demographic, military, religious, physical, psychosocial, and behavioral characteristics were assessed in a convenience sample of ADM. Over 84% reported high levels of one or more MI symptom and 52% indicated 4 or more symptoms at this severity level. Religiosity was inversely related to MI in bivariate analyses ( r = -.20, p < .05), although this relationship was explained by age in multivariate analyses. PTSD severity did not moderate this relationship, although it tended to be stronger in older participants with more severe PTSD ( r = -.30, p < 0.15). Among those with significant PTSD, two-thirds were interested in a spiritually-integrated treatment for their MI. Symptoms of MI were common in these ADM. Although religiosity was not associated with MI, the majority were interested in a spiritual approach to their symptoms.